Pemberdayaan Kader Posyandu tentang Deteksi Dini Stunting, Stimulasi Tumbuh Kembang dan Gizi Seimbang Balita - Yossy Utario; Misniarti Misniarti; Sri Haryani (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Stunting is a condition where toddlers have a body length or height that is less than their age. Stunting can have an impact on growth and development both in the long term and, so it needs prevention or treatment. Posyandu cadres play an important role in preventing and overcoming stunting in the community. This activity aimed to provide education to posyandu cadres about early detection of stunting, stimulation of growth and development and balanced nutrition of toddlers. The method used were education through lectures and discussions, simulation practices, and mentoring cadres to families of stunting toddlers. The activity was attended by 10 cadres and assistance to 20 mothers of stunting toddlers. The data obtained showed an increase in the knowledge and skills of cadres and mothers of stunting toddlers regarding early detection of stunting, stimulation of growth and development, and balanced nutrition in toddlers. Empowerment of posyandu cadres needs to be carried out on an ongoing basis, especially as an effort to improve the knowledge and skills of cadres, as an effort to prevent and deal with stunting.